THE ROLE OF THE INTERNET IN IMPROVING THESIS COMPILATION MOTIVATION FOR NURSING STUDENTS - Jhoanda Bahtiar Pratama; Shindi Hapsari; M Jamaluddin (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2026)
The advancement of information technology, particularly the internet, has transformed the learning process in higher education, not only as a source of information but also as a medium for academic communication. However, studies specifically examining the role of the internet as a communication medium in influencing thesis-writing motivation among nursing students remain limited. This study aimed to analyze the relationship between internet use as a communication medium and thesis-writing motivation among undergraduate nursing students at Universitas Muhammadiyah Semarang. This study employed a quantitative analytic design with a cross-sectional approach. A total of 48 students were selected using purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using Spearman’s Rho test. The results showed a significant relationship between internet use as a communication medium and thesis-writing motivation (p < 0.05). These findings indicate that optimizing the use of the internet as an academic communication medium can enhance students’ motivation in completing their thesis. This study contributes to the development of digital-based learning strategies, particularly in improving the effectiveness of academic supervision in nursing education.Keywords: internet, communication media, motivation, final project, nursing students